DISTRIBUSI SUHU BAWAH PERMUKAAN MANIFESTASI PANAS BUMI UNTUK ANALISIS GRADIEN SUHU DI BUKIT KASIH KANONANG - Anisa Bilondatu; Treesje Londa; Cryke Bujung (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
The existence of geothermal resources below the surface can be shown, among others, by the presence of land which has a temperature higher than the surrounding soil temperature. This occurs due to the conduction of heat transfer from subsurface rocks to surface rocks. How is the temperature distribution below the surface, and the temperature gradient pattern of geothermal manifestations in Bukit Kasih Kanonang, is interesting to study considering that the area is a tourist area as well as a natural laboratory for the geothermal system. The research objective was to determine the subsurface temperature distribution of geothermal manifestations and temperature gradient patterns in the tourist area of ​​Bukit Kasih Kanonang. Data collection was carried out by means of direct measurements in the field. Measurements were made at 20 measuring points with a depth of 3 cm, 9 cm, and 15 cm respectively. Data processing using Ms. software. Office Excel and Surfer 12. The results showed that the geothermal manifestations in the tourist area of ​​Bukit Kasih Kanonang had an average temperature range of 3.83 0C to 97.97 oC at a depth of 3 cm, 48.43 0C to 96.93 0C at a depth of 9 cm, and 52.9 0C to 96 ,60C at a depth of 15 cm. The temperature gradient increases with each depth. Linear temperature gradient in the morning.